THE EFFECT OF COCOA POD BORER (CONOPHOMORPA CRAMERELLA) ON COCOA PRODUCTION - Silalahi, Azis Amarta (Journal of Agriculture, 2022)
Cocoa fruit borer attacks all stages of fruit, namely young fruit, mature fruit and ripe fruit. Symptoms of attack on young fruit are indicated by the appearance of large yellow spots on the skin of the affected fruit. His attacks cause an average production drop of 50% with a range of 10% to 90%. The basic method in this writing is descriptive. The data used are the results of previous studies relating to the attack of CPB pests on the decline in cocoa fruit production. The results of the discussion, it can be concluded that the attack of the cocoa pod borer (PBK) is very influential on annual cocoa production. Yield losses due to CPB attacks ranged from 18.25% to 73.04%. However, CPB pests can be controlled through good technical culture measures during cocoa plantation management.